Diagnosis on dilemma: Arteriovenous malformation with scar pregnancy with old retained product of conception (Indian Journal of Case Reports, 2024)
Cesarean scar pregnancy (CSP) is described as the placement of a gestational sac within the scar from a previous cesarean operation and is considered an ectopic pregnancy. Ectopic pregnancy situated in a cesarean section scar is a rare but potentially life-threatening event. Because of its rarity, there are no universal guidelines to manage this condition. CSP has no pathognomonic signs or symptoms and its presentation varies considerably. Here, we report a case of scar pregnancy containing an old retained product of conceptus.